Penerapan Prinsip-Prinsip Kepesantrenan Pada Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta Menurut Undang-Undang Kepesantrenan - Rifky Ijlal Musyaffa; Hilalludin Hilalludin; Muhammad Fikri Hidayat; Yusuf Adi Prianto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research examines the implementation of Law Number 18 of 2019 concerning Pesantren in Indonesia, focusing on Sekolah Tinggi Ilmu Tarbiyah Madani (STITMA) as a case study. The background of the study covers the historical evolution of pesantren from traditional Islamic boarding schools to legally regulated modern institutions. The research aims to understand how the law affects the functions of education, Islamic preaching (dakwah), and community empowerment at STITMA. A qualitative method was employed with primary data gathered through observations and secondary data sourced from literature studies. Findings indicate that the law has increased awareness of the importance of religious education, expanded educational access for pesantren graduates, and provided a framework for independent financial management at STITMA. The implications of this research underscore the need for more effective socialization of the law across different regions and addressing the stigma associated with pesantren as potential centers of radicalism.